On the identity of Julus rimosus Karsch, 1881 (Diplopoda, Julida, Julidae), the only schizophylline known from Libya (North Africa) and notes on Libyan millipedes - Akkari, Nesrine (Zootaxa, 2013)
The first millipede recorded from Libya was a male julid, described by Karsch (1881) from Jebel Tarrhuna, Bir Milrba as Julus rimosus Karsch, 1881. The original description of rimosus was mainly based on coloration. The gonopods were however briefly described as brown, with a long yellow curved thread (“corpore genital fusco, filo flavo, curvato, longo”). Karsch (1881) additionally provided two figures illustrating the telson and gonopods (figs 4, 4b) with a remark stating that the species is similar to Julus lapidarius, 1846 (now Ommatoiulus lapidarius) of which only females were hitherto described by Lucas (1846). Subsequently, Silvestri (1896) providing a comprehensive list of all myriapods of Tunisia, presented an overview of North African fauna and proposed new synonymies for several species. Among these, Silvestri (1896) considered Julus rimosus as a junior synonym of Julus lapidarius Lucas, 1846 (now Ommatoiulus lapidarius). Silvestri (1896: 160) was obviously not sure about the identity of rimosus, except that he was convinced that the gonopods, as illustrated by Karsch (1881), definitely were not representative of an ‘Julus’ species: “Karsch described J. rimosus and provided at the same time an illustration of the male copulatory organ, but what the devil he mistook for this organ I cannot say. It is certain that that figure cannot even be remotely representative of Julus. Fortunately I was able to examine the individuals of Julus he determined as J. rimosus and I found that this species is none other than J. lapidarius Lucas” (translated from Italian).